Modelling Digital Marketplace for SME’s in Construction Industry - Fitria, Hanin; Hakim, Cikita Berlian; Muadzah, Muadzah (PT. SAFARI AMALIA, 2024)
Small and Medium Enterprises (SMEs) play a crucial role in the construction industry in Indonesia, with construction SMEs accounting for nearly 90% of the total construction industry. However, construction SMEs face various challenges, such as limited resources, lack of access to projects, inefficient procurement processes, and human resource issues. This research aims to model a digital marketplace specifically designed to address these challenges and develop the business models of construction SMEs. By employing the Business Model Canvas (BMC) approach, this research maps nine key elements in designing the business model of a digital marketplace for construction SMEs, including customer segments, value propositions, distribution channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structure. The results indicate that a digital marketplace can serve as a solution for construction SMEs to improve project access, process efficiency, and collaboration with strategic partners. Through the digital marketplace, construction SMEs can promote their products and services, connect with consumers and project partners, and enhance their capacities and competencies. This model offers a roadmap for developers and policymakers in creating platforms that drive competitiveness, efficiency, and growth of construction SMEs in the era of industrial digitalization..